The Adoration of the Magi - Stone, George Eathl (photographer):::Creator::::::::::::
Photograph depicting the left diptych leaf of the visit of the Magi, 14th Century, France. Photograph taken in the Bargello National Museum, Florence, Italy, 1941. Artist unknown.